AHMAD DONISHNING EDUCATIONAL ISSUES AT NATURAL SCIENCES SCHOOL IN "NAVODIR UL-WAKOE" ASAR - Муродалиева Шахнозахон Махмудовна; Наимов Исмат Нусратуллоевич (Galaxy International Interdisciplinary Research Journal, 2023)
Such as raising the future generation’s respect for our morally sound national values and the love for the Motherland are important issues of today’s pedagogy. In this article, the topic of educational issues in the field of natural sciences is presented in the work “ Navadir ul- vakoe” by the great thinker of encyclopedic knowledge Ahmad Donish. The authors note that until today this topic has not been scientifically studied by researchers, this work of a great thinker analysed the scientific thougts on education.